Generation Change of Cropping Intensity in Bangladesh: A Systematic Review - , Hasib Bin Saif; , Kanis Fatema Ruma; , Istiak Ahmed; , Md. Riazul Islam; , Afsana Hoque Akhi; , Fardus Ahamed Nasim; , Rafia Akhtar Rimu; , Md. Rezaul Karim (Archives of Current Research International, 2024)
The cropping intensity in Bangladesh remained stagnant until the late 18th century, then surged notably during the period of 1987–88 and 2010–11. Cropping intensity increased from 143% to 173.06% with an annual growth rate of 1.20% in the first half of Bangladesh's 50 years of independence. During that period, net cropped area fell from 8248.16 thousand hectares to 7806.07 thousand hectares, while gross cropped area increased from 11785.55 thousand hectares to 13518.64 thousand hectares. In the second half of 50 years, cropping intensity has increased from 173.06 to 198.00 with an increasing rate of 0.99% per year, in this time both net and gross cropped area increased. Overall, within the 50 years of Bangladesh's independence, cropping intensity has increased from 143% (1971-72) to 198% (2019-20) with an increasing rate of 1.10% per year and will be 211.03 % (projected) by 2030. At that time net cropped area decreased from 8248.16 thousand hectares to 8126.00 thousand hectares but grossed cropped area increased from 11785.55 thousand hectares to 16057.00 thousand hectares. This overall change in cropping intensity is due to an increase in double (17.11%) and tripled cropped area (18.37%) and a decline in single cropped area (-35.76%). Shifting from single to multiple cropping attributed to this change. New short-duration cultivars tailored to fallow time drove intensity. However, limited climate-smart solutions and management practices posed hindrances. Examining rice yield extension, this study used historical and projected trends to forecast 2030 cropping intensity. New four cropped-based CP has also been introduced which occupied 0.28% of the net cropped area and definitely will play a vital role to increase cropping intensity in the future.